2009
DOI: 10.1002/cctc.200900057
|View full text |Cite
|
Sign up to set email alerts
|

Shape‐Selective Conversion of Methanol to Hydrocarbons Over 10‐Ring Unidirectional‐Channel Acidic H‐ZSM‐22

Abstract: With the forecasted depletion in global oil reserves, new routes to petrochemical products from natural gas, coal, or biomass are becoming increasingly important. The methanolto-hydrocarbons (MTH) reaction constitutes the final step in one such route. The MTH reaction proceeds over Brønstedacidic zeolite or zeotype catalysts, and near-commercial processes exist for the methanol-to-gasoline (MTG) reaction over ZSM-5, as well as the methanol-to-olefin (MTO) reaction over A breakthrough in the mechanistic unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
133
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(156 citation statements)
references
References 18 publications
17
133
0
6
Order By: Relevance
“…In the one-dimensional pores of H-ZSM-22 only alkenes were found to be active HP species resulting in the production of branched C 5+ alkenes, [72][73][74][75][76][77][78] whereas aromatics were found to be dominating HP species in H-SAPO-34 and large pore zeolites H-beta and H-SSZ-24. 22,24,[79][80][81][82] A high activity of aromatics is mostly coupled with a high selectivity towards ethene and propene.…”
Section: Catalysis Science and Technology Papermentioning
confidence: 99%
See 1 more Smart Citation
“…In the one-dimensional pores of H-ZSM-22 only alkenes were found to be active HP species resulting in the production of branched C 5+ alkenes, [72][73][74][75][76][77][78] whereas aromatics were found to be dominating HP species in H-SAPO-34 and large pore zeolites H-beta and H-SSZ-24. 22,24,[79][80][81][82] A high activity of aromatics is mostly coupled with a high selectivity towards ethene and propene.…”
Section: Catalysis Science and Technology Papermentioning
confidence: 99%
“…Several experimental studies clearly pointed out that methanol conversion in H-ZSM-22 occurs through the alkene cycle and that aromatic HP species are not active. [73][74][75]77,78,125 Cui et al…”
Section: Concertedmentioning
confidence: 99%
“…Nearly complete conversion of methanol could be obtained over ZSM-22 at 450 • C (WHSV = 10 h −1 ) [21]. In a very recent report from the group of Olsbye [22], they also found that under suitable conditions ZSM-22 has a conversion capacity comparable to that of SAPO-34. These results have been somewhat contradictive with the report of Cui et al [18].…”
Section: Introductionmentioning
confidence: 89%
“…[3][4][5] Zeolites have well-defined molecular-sized pores, in which shape-selective adsorption and catalysis can occur. [3][4][5][6][7][8][9][10][11] Recently, there is great interest in organic zeolites constructed with organic and organometallic building blocks because they can have flexible channels when appropriate organic functional groups are used, leading to unique selective-inclusion properties. 1,2,12 Ionic crystals of polyoxometalates are nanostructured materials that are capable of selectively absorbing molecules.…”
mentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20] The absorption properties are finely controlled by adjusting the charge of the polyoxometalates and the organic moiety of the macrocations. For example, K 3 [Cr 3 O(OOCH) 6 solution with vigorous stirring. The resulting solution was allowed to stand for 1 day at room temperature, during which time a white solid precipitated.…”
mentioning
confidence: 99%